Diagnóstico diferencial das enfermidades do sistema nervoso de bovinos no serviço de defesa sanitária de Minas Gerais - Taismara Simas de Oliveira (2012)
This work is based on retrospective and prospective analysis of biological samples from cattle that had died after neurological symptoms, which were collected in Minas Gerais from 2003 to 2010 and sent to Instituto Mineiro de Agropecuária. The samples were analyzed b y direct immunofluorescence and biological test for rabies, histopathology, immunohistochemistry, PCR for bovine herpesvirus -1, bovine herpesvirus type-5, herpesvirus sheep type 2, porcine herpesvirus type-1, Listeria monocytogenes and Histophilus somni; toxicologic tests for pesticides and other toxic agents; and mice soroneutralization for detection of botulinum toxin. Parameters related to cattle and samples were assessed. Frequency of positivity for the techniques used and distribution were determined, and the results were analyzed by Fisher's exact test. In conclusion, cattle samples submitted to Instituto Mineiro de Agropecuária partially meet the requirements for surveillance of rabies and transmissible spongiform encephalopathies.The frequency of bovine rabies diagnosed in Minas Gerais was influenced by breed, age and type of death of the affected animal as well as composition of the sample. Other neurological diseases are present in Minas Gerais and the use of multiple diagnostic techniques allowed a more accurate differential diagnosis and a higher rate of conclusive diagnoses.